Development of Virtual Reality-Based Learning Media for Product-Setting Subjects in Vocational Schools - Rahmadi, Andi; Hanafi, Ivan; Sukardjo, Sukardjo (Journal of World Science, 2023)
The research aims to develop learning media based on Virtual Reality for the Product Management subject at SMKN 14 Jakarta. The study uses research and development methods (Research & Development) using the combined procedure reference development model between the Borg and Gall models, the Dick Carey Model), and the Hannafin and Peck Models. This model is carried out through needs analysis, design, development, testing, implementation, and maintenance. The results of this study are as follows. (In summary, the research went through several key stages: 1) The analysis stage highlighted the limitations of practical facilities for the Limited Product Arrangement subject. 2) The design phase resulted in a comprehensive design, including Virtual Reality illustrations with 3D display designs, color selection, typography, page layouts, images, videos, audio, and interface designs. 3) During the development of Virtual Reality products, the researcher processed the content into a medium using the Unity Engine application. 4) The testing phase, which included material and media testing, produced highly favorable results. Material experts rated content quality and objectives at 4.8 in the "very feasible" category, while media experts found functional suitability very doable with a percentage score of 4.67. Usability testing yielded a score of 4.7, indicating good usability. Performance efficiency met standards and effectively engaged students' learning interest. Overall, these findings demonstrate the success of the research in developing Virtual Reality-based learning materials for the Product Arrangement subject.